Bronchoscopically Delivered Thermal Vapor Ablation of Human Lung Lesions. Issue 2 (April 2019) - Ferguson, J. Scott; Henne, Erik
Abstract : Background: The discovery that early diagnosis can reduce the mortality of lung cancer provides firm evidence that early surgical intervention is effective. However, surgical resection is available only to those who are healthy enough to tolerate the procedure. Vapor ablation may provide an additional method of treating the lung cancer patient, and has been studied in humans for emphysema treatment. In swine, we previously demonstrated that bronchoscopically delivered thermal vapor ablation (BTVA) could be accurately applied, was uniform, anatomically confined, and was tolerated by the animal. To provide evidence that BTVA may be a feasible method of treatment in humans, and since human and swine lungs have differing airway and segmental anatomy, we extended our studies to deceased human lungs to determine if anatomically confined and uniform ablations could be obtained with levels of energy comparable with our swine and human emphysema studies. Methods: We obtained fresh, deceased human lungs and performed BTVA with increasing energy in subsegmental regions of lung containing tumors as well as non–tumor-containing areas in order to determine if uniform ablations with sharp boundaries could be obtained in human lung. Results: We found that all ablations were anatomically contained. The frequency of uniform ablation effect was dependent on the total energy delivered and was achieved at a greater frequency than those with sharp boundaries. If a lung tumor was contained within the anatomy of the subsegment, the ablation zone completely surrounded the tumor. Conclusion: We conclude that BTVA may have a future role in the treatment of lung cancer and should be investigated further in clinical trials.